ASPEK BAHASA SEBAGAI PEMBEDA ANTARA KEMU'JIZATAN AL-QUR’AN DAN BUKTI-BUKTI KEBENARANNYA - Baihaqi, Yusuf (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
There is ambiguity in identifying the aspects of al-Qur’an miracles, that is caused by no clear difference in understanding the aspects of al-Qur’an miracles and the justification. To understand those two aspects, the aspect that makes al-Qur’an as a holy script that have miracles and the aspect that justify that al-Qur’an is from Allah swt, there is an important step so that we will not be entrapped in the ambiguity. In addition, there is a difference among the ulama (Islamic scholars) in formulating the aspects of miracle in al-Qur’an. This is a difference emerging at the early generation of Islamic development. Along the history, the difference is more and more varied. Language aspect is the only aspect that makes al -Qur’an as a holy script having miracle. While the content of al -Qur’an such as the news of ghaib, law completeness, and Allah’s miracle spread in the universe has no relationship with the challenge implied to the miracle, instead the miracle in the content of al-Qur’an as part of the proof justifying that al-Qur’an is from Allah swt.